2010
DOI: 10.5152/akd.2010.116
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and other imaging modalities in pulmonary arterial hypertension

Abstract: It is essential to diagnose pulmonary arterial hypertension in early stages of the disease. However, most patients have late diagnosis due to the lack of disease-specific symptoms and prominent findings. Although cardiac catheterization is the gold standard in the diagnosis of pulmonary arterial hypertension, noninvasive diagnostic modalities do also have major roles in the diagnosis, risk assessment and follow-up of the patients with pulmonary arterial hypertension. The focus of the present review is the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
4
1
2
Order By: Relevance
“…Studies suggest that severe OSA is independently associated with pulmonary hypertension in direct relationship with disease severity and application of CPAP reduces pulmonary systolic pressure levels (28). The E/Em ratio described as a predictor of left atrial pressure was also found to be reduced in our study however, the observed difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies suggest that severe OSA is independently associated with pulmonary hypertension in direct relationship with disease severity and application of CPAP reduces pulmonary systolic pressure levels (28). The E/Em ratio described as a predictor of left atrial pressure was also found to be reduced in our study however, the observed difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…TAPSE reflects the right ventricle systolic function, whereas Tei shows both systolic and diastolic functions (31,32). In our study, TAPSE was found significantly different between groups, but the difference of Tei index was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Ekokardiyografik tekniklerden biri olan triküspit anüler plan sistolik hareket (TAPSH)'nin pulmoner hipertansiyonlu hastalarda prognostik önemi olduğu gösterilmiştir. [15] Normofonksiyone sağ ventrikülde, triküspit kapak anülüsü sistol esnasında apekse doğru 15-20 mm yaklaşır. Bu TAPSH'nin normal değeridir.…”
Section: Discussionunclassified